2017
DOI: 10.1186/s13195-017-0247-9
|View full text |Cite
|
Sign up to set email alerts
|

Structured relearning of activities of daily living in dementia: the randomized controlled REDALI-DEM trial on errorless learning

Abstract: BackgroundErrorless learning (EL) is a method for optimizing learning, which uses feed-forward instructions in order to prevent people from making mistakes during the learning process. The majority of previous studies on EL taught patients with dementia artificial tasks of little or no relevance for their daily lives. Furthermore, only a few controlled studies on EL have so far been performed and just a handful of studies have examined the long-term effects of EL. Tasks were not always trained in the patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 21 publications
1
29
0
4
Order By: Relevance
“…A different, but related, approach to improving everyday functioning involves structured training in completing selected activities of daily living. Two recent trials 35,36 found that performance on trained tasks improved, although there was no evidence of generalisation to everyday situations 35 of CR 37 reported that, compared with usual treatment, CR participants showed less functional decline at 24 months, a 6-month delay in institutionalisation and lower overall rates of institutionalisation, but no significant differences mood or quality of life. The CR intervention in that trial was poorly described, and goal attainment was not directly measured.…”
Section: How the Findings Relate To Other Evidencementioning
confidence: 99%
“…A different, but related, approach to improving everyday functioning involves structured training in completing selected activities of daily living. Two recent trials 35,36 found that performance on trained tasks improved, although there was no evidence of generalisation to everyday situations 35 of CR 37 reported that, compared with usual treatment, CR participants showed less functional decline at 24 months, a 6-month delay in institutionalisation and lower overall rates of institutionalisation, but no significant differences mood or quality of life. The CR intervention in that trial was poorly described, and goal attainment was not directly measured.…”
Section: How the Findings Relate To Other Evidencementioning
confidence: 99%
“…The 13 studies with lower ROB were conducted in the United Kingdom, 26,30,[37][38][39] United States, 29,31 Netherlands, 34,56 Finland, 27,28,33 Germany, 32,36 Denmark, 25 and France. 35 .…”
Section: Description Of Lower Rob Studiesmentioning
confidence: 99%
“…35 . They evaluated functional ability using informant or self-report scales that measured patient performance and dependency on others to perform ADLs, [25][26][27][28][29][30][31][32][33][35][36][37][38][39]56 activity-specific goal setting, 56 and physical role function. 34 We divided the included studies into four groups: physical exercise therapies, OT interventions, multicomponent interventions, and cognitionoriented or reminiscence therapies.…”
Section: Description Of Lower Rob Studiesmentioning
confidence: 99%
“…"geführte Lernen" (vorsagen, vormachen, korrigieren) dem sog. "aktiven Lernen" (ausprobieren lassen) in der Begleitung von Personen mit Alzheimer-oder gemischter Demenz in der eigenen Häuslichkeit überlegen ist [11]. Hintergrund ist die Überlegung, dass geführtes Lernen (errorless learning) mehr prozedurale Lernsysteme anspricht, wogegen aktives Lernen (trial and error) mehr auf explizite, hippokampale Gedächtnisleistungen angewiesen ist.…”
Section: Kognitive Verfahrenunclassified
“…In beiden Gruppen verbesserte sich die Performance der Aktivitäten des täglichen Lebens. Im Ergebnis zeigte sich jedoch kein Unterschied zwischen geführtem und aktivem Lernen [11].…”
Section: Kognitive Verfahrenunclassified